Empowering Employees to Maximize Their Performance is a Key Factor in Achieving Excellence - Benny Chandra; Anoesyirwan Moeins; Marhalinda Marhalinda (Greenation International Journal of Economics and Accounting, 2024)
The primary goal of this study is to comprehensively examine and evaluate multiple elements, namely: (1) Leadership, (2) Empowerment, (3) Performance, and (4) The impact of Leadership and Empowerment on the performance of Employees at PT Citra Teknik Medika in Bandung City. Both the simultaneous and partial effects will be taken into account during the analysis. To conduct this research, a combination of descriptive and explanatory surveys was utilized as the research methods. The employees of PT Citra Teknik Medika in Bandung were selected as the unit of analysis, with a sample size of 33 individuals. This investigation follows a causality approach and adopts a cross-sectional time frame. Upon examination of the study's results, it became evident that the workforce at PT Citra Teknik Medika in Bandung City possessed diverse viewpoints regarding leadership. The majority of employees responded favorably, although the overall level of empowerment within the organization was deemed less than satisfactory. In regard to performance, the employees of PT Citra Teknik Medika displayed a positive trajectory. Additionally, the study unveiled that both leadership and empowerment jointly contribute to employee performance. However, when analyzed individually, it was determined that leadership has a more significant influence on performance than empowerment. When seeking to improve overall performance, it is crucial to prioritize empowerment as it has a significant impact. Hence, it is highly recommended that the employees of PT Citra Teknik Medika in Bandung City make empowerment their top priority and actively participate in ongoing initiatives. This will enable them to enhance their skills and conduct their work with greater proficiency and professionalism